Determination of aliskiren in human serum quantities by HPLC–tandem mass spectrometry appropriate for pediatric trials. (10th October 2012) - Burckhardt, Bjoern B.; Ramusovic, Sergej; Tins, Jutta; Laeer, Stephanie
ABSTRACT The orally active direct renin inhibitor aliskiren is approved for the treatment of essential hypertension in adults. Analytical methods utilized in clinical studies on efficacy and safety have not been fully described in the literature but need a large sample volume ranging from 200 to 700 μL, rendering them unsuitable particularly for pediatric applications. In the assay presented only 100 μL of serum is needed for mixed‐mode solid‐phase extraction. The chromatographic separation was performed on XselectTM C18 CSH columns with mobile phase consisting of methanol–water–formic acid (75:25:0.005, v/v/v) and a flow rate of 0.4 mL/min. Running in positive electrospray ionization and multiple reaction monitoring the mass spectrometer was set to analyze precursor ion 552.2 m/z [M + H]+ to product ion 436.2 m/z during a total run time of 5 min. The method covers a linear calibration range of 0.146–1200 ng/mL. Intra‐run and inter‐run precisions were 0.4–7.2 and 0.6–12.9%. Mean recovery was at least 89%. Selectivity, accuracy and stability results comply with current European Medicines Agency and Food and Drug Administration guidelines. This successfully validated LC‐MS/MS method with a wide linear calibration range requiring small serum amounts is suitable for pharmacokinetic investigations of aliskiren in pediatrics, adults and the elderly. Copyright © 2012 John Wiley & Sons, Ltd.